PENGARUH PRODUKTIVITAS KERJA DAN TINGKAT PENDIDIKAN TERHADAP PENDAPATAN PERKAPITA PENDUDUK DI KABUPATEN/KOTA PROVINSI BALI - Ratnasari, Ni Made Ayu; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
One indicator to see the welfare of the population is income per capita. Income per capita the more likely the region has high level of development and income the average population can improve their welfare. But there still a disparity income between regencies / cities in Province of Bali from the Gini ratio. The objectives of this study are 1) Analyzing effect of work productivity and education level on income per capita of residents in districts / cities of Bali Province 2) Analyzing level of education moderating work productivity on the income per capita residents in districts / cities of Bali Province. The data used in this research is secondary data. This research was carried out using non-participant observation methods. Data analysis techniques used panel data estimation and moderated regression analysis. The results are 1) Work productivity and education level have a positive and significant effect on the income per capita of residents in districts / cities of Bali Province. 2) The level of education strengthens the effect of work productivity on per capita income of the population in the regencies / cities of the Province of Bali.   Keywords: per capita income of the population, work productivity, education level